###### Asked in Math and ArithmeticAlgebraGeometry

Math and Arithmetic

Algebra

Geometry

# What are some examples of how to use the quadratic formula?

## Answer

###### Wiki User

###### May 01, 2010 6:37AM

For a quadratic equation in the form: ax² + bx + c = 0

The quadratic formula comes from completing the square of the quadratic equation that gives you a result of x=-b±√b²-4ac divided by 2a.

Using a simple quadratic equation like x² + 2x + 1 = 0

a=1; b=2; c=1

x=-2±√2²-4(1)(1) divided by 2a

x=-2±√4-4 divided by 2a (4 - 4 = 0 and the square root of 0 is 0)

Therefore, x=-2

## Related Questions

###### Asked in Math and Arithmetic, Algebra, Calculus

### Find all complex solutions for the equation x2 equals 4x - 29?

Use the quadratic formula. In x2 - 4x + 29 = 0, a is 1, b is -4,
c = 29. The quadratic formula is: x = (-b plusminus squareroot(b2 -
4ac)) / 2a
Use the quadratic formula. In x2 - 4x + 29 = 0, a is 1, b is -4, c
= 29. The quadratic formula is: x = (-b plusminus squareroot(b2 -
4ac)) / 2a
Use the quadratic formula. In x2 - 4x + 29 = 0, a is 1, b is -4, c
= 29. The quadratic formula is: x = (-b plusminus squareroot(b2 -
4ac)) / 2a
Use the quadratic formula. In x2 - 4x + 29 = 0, a is 1, b is -4, c
= 29. The quadratic formula is: x = (-b plusminus squareroot(b2 -
4ac)) / 2a

Load More